Incidence and antibiogram of Vibrio parahaemolyticus in processed and frozen bivalve mollusks in Kuala Terengganu, Malaysia - Tang, John Yew Huat; Wan Rosli, W. F.; Abdul Razak, N. H.; Yeo, Chew Chieng; Abu Bakar, Che Abdullah; Radu, Son (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2014)
This study aimed to investigate the prevalence and antibiogram of Vibrio parahaemolyticus in processed bivalve molluscs in Kuala Terengganu. A total of 80 seafood samples, namely mussels (n=20), carpet clams (n=20), cockles (n=20) and scallops (n=20), were subjected to PCR and conventional plating method for the detection of V. parahaemolyticus. V. parahaemolyticus was found in green mussels (55%), carpet clam (80%), cockles (40%) and scallops (55%). Fifty-five V. parahaemolyticus isolates were subjected to 9 types antibiotic sensitivity test using discs diffusion method. All isolates were susceptible to Tetracycline and Gentamycin. Isolates showed high resistance towards Vancomycin (52.73%), Penicillin (45.45%) and Amplicillin (32.73%). Resistance towards Amikacin, Ciprofloxacin and Norfloxacin were found to be 1.82%. It can be concluded that local bivalve molluscs were contaminated with V. parahaemolyticus and isolates showed resistance towards certain antibiotics. Therefore, consumption of raw or semi-cooked bivalve molluscs is not advisable.